2015
DOI: 10.3389/fpsyg.2015.01525
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of embodiment

Abstract: This paper is a critical review of recent studies demonstrating the mechanism of sensorimotor simulation in different cognitive domains. Empirical studies that specify conditions under which embodiment occurs in different domains will be discussed and evaluated. Examples of relevant domains are language comprehension (Tucker and Ellis, 1998), autobiographical memory (Dijkstra et al., 2007), gestures (Alibali et al., 2014), facial mimicry (Stel and Vonk, 2010), and problem solving (Wiemers et al., 2014). The fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 76 publications
0
50
0
Order By: Relevance
“…In contrast, given that faces expressing pain reflect the experience of pain more indirectly, through facial action units (Williams, ), they may trigger similar activation in the neural network involved in pain perception in controls and participants with ASD. In addition, although both the observation of facial expressions and bodily movements trigger embodiment mechanisms (Dijkstra & Post, ), they might do so through slightly different pathways. It is possible that the embodiment pathway triggered by facial expressions is intact in ASD, but that the embodiment pathway triggered by bodily movement is altered.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, given that faces expressing pain reflect the experience of pain more indirectly, through facial action units (Williams, ), they may trigger similar activation in the neural network involved in pain perception in controls and participants with ASD. In addition, although both the observation of facial expressions and bodily movements trigger embodiment mechanisms (Dijkstra & Post, ), they might do so through slightly different pathways. It is possible that the embodiment pathway triggered by facial expressions is intact in ASD, but that the embodiment pathway triggered by bodily movement is altered.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the general agreement on the function of conceptual knowledge for object recognition, language and action planning. (Tulving, 1972; Humphreys et al, 1988; Pulvermüller, 1999; Barsalou et al, 2003; Kiefer and Pulvermüller, 2012), it is controversially debated how the conceptual system is functionally organized and implemented in the human brain (for reviews see, Kiefer and Pulvermüller, 2012; Dijkstra and Post, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…According to the AAE model, indeed, reducing the distance between the self and the stimulus is indicative of acceptance, whereas increasing the distance is indicative of refusal. Thus the AAE generally manifests as top-down motor compatibility effect, because it occurs in tasks where body movements are used to indicate one's evaluations of stimuli, with motor responses being facilitated when they correspond to simulated actions and are hindered when there is no correspondence between the two (Dijkstra & Post, 2015).…”
Section: Approach and Avoidance Effectsmentioning
confidence: 99%
“…Many scholars have shown that both the processing and production of gestures are based on the instantaneous, automatic and unconscious mechanism of sensorimotor simulation (Gallese & Goldman, 1998;Gallese, 2001;Moors & De Houwer, 2006;Hostetter & Alibali, 2008;Shtyrov, Butorina, Nikolaeva & Stroganova, 2014). This mechanism has its roots in the kinesthetic imitation (Meltzoff & Gopnik, 1993;Chartland & Bargh, 1999;Dijksterhuis & Bargh, 2001), is influenced by experience (Zwaan & Madden, 2005;Zwaan & Taylor, 2006;Pecher & Winkielman, 2013) and is considered one of the main mechanisms underlying embodiment effects found in cognitive processing (Dijkstra & Post, 2015).…”
Section: Introductionmentioning
confidence: 99%